1078. Optimization of a 96-well Plate Format Assay to Evaluate Concentration-Dependent Activity of a Monoclonal Antibody Against the O Antigen O25b from ST131-H30 Escherichia coli. (4th December 2021) - Lindley, Jill; Doyle, Timothy B; VanScoy, Brian D; Rubino, Christopher M; Bhavnani, Sujata M; Ambrose, Paul G; Castanheira, Mariana; Castanheira, Mariana
Abstract: Background: Escherichia coli ST131 is a major challenge for global human health. Among ST131 isolates, the H 30 type is prevalent and displays multiple drug resistance to classes. A monoclonal antibody (mAb) specific for the O antigen, O25b, which is conserved in ST131- H 30 clonal lineage, was developed for diagnostic and prophylactic therapy. We optimized a 96-well plate assay to test different concentrations of the mAb against E. coli clinical isolates. Methods: Initial growth curves were performed against 69 ST131-O25b, 9 ST131-O25a, 32 ST131 non-O25, and 29 non-ST131 E. coli isolates in 40% active human serum (HS). Additional conditions evaluated for growth inhibition by the mAb included 3 media types, 3 HS sources, pH variations, addition of polysorbate 80 (P80), inoculum concentration, length of incubation, and varying calcium and magnesium concentrations. Once optimal parameters were established, the assay was miniaturized into a 96-well format and 12 ST131-O25b and 5 non-ST131 were tested. Fluorescence and visual reading using alamarBlue (AB), a cell metabolism indicator, were performed at 8 and 10h in addition to plating for viable colonies. Results: After 10h incubation, only 36/69 (52.2%) ST131-O25b isolates exhibited visible growth in BHI plus 40% HS. A 2-part growth inhibition assay using BHI plus 50% HS and BHI with 25% HS without the addition of P80, calcium, or magnesium was considered the optimal growth condition for EC strains to test the effect of the mAb. By 10 hours, all ST131-O25b strains displayed a visual inhibition of growth between 0.3-5 mg/L of α-ST131 mAb and zero non-ST131 strains were inhibited (Figure). While reading AB on a fluorometer was more sensitive and less subjective than visual interpretation, both reading methods allow for endpoint determinations. Additionally, panels were able to go through one freeze-thaw cycle and still retain α-ST131:O25b mAb activity. Conclusion: Concentration-dependent activity of a α-ST131:O25b mAb can be measured in vitro in a microtiter format; however, the growth inhibition by HS, while still providing enough complement for complement-mediated mAb killing, might be an obstacle. Additionally, assay reproducibility may be difficult without a consistent source of active HS. Figure Disclosures: Jill Lindley, Bravos Biosciences (Research Grant or Support)ContraFect Corporation (Research Grant or Support)Pfizer, Inc. (Research Grant or Support)Qpex Biopharma (Research Grant or Support) Timothy B. Doyle, AbbVie (formerly Allergan ) (Research Grant or Support)Bravos Biosciences (Research Grant or Support)GlaxoSmithKline (Research Grant or Support)Melinta Therapeutics, Inc. (Research Grant or Support)Pfizer, Inc. (Research Grant or Support)Shionogi (Research Grant or Support)Spero Therapeutics (Research Grant or Support) Brian D. VanScoy, B.S., 3-V Biosciences (Grant/Research Support)Achogen (Grant/Research Support)Amplyx Pharmaceuticals, Inc. (Grant/Research Support)Arixa Pharmaceuticals (Grant/Research Support)Arsanis Inc. (Grant/Research Support)B. Braun Medical Inc. (Grant/Research Support)Basilea Pharmaceutica (Grant/Research Support)BLC USA (Grant/Research Support)Boston Pharmaceuticals (Grant/Research Support)Bravos Biosciences, LLC (Grant/Research Support)Cidara Therapeutics Inc. (Grant/Research Support)Cipla, USA (Grant/Research Support)Corcept Therapeutics (Grant/Research Support)Cumberland Pharmaceuticals (Grant/Research Support)Debiopharm International SA (Grant/Research Support)Discuva Limited (Grant/Research Support)Emerald Lake Technologies (Grant/Research Support)Enhanced Pharmacodynamics (Grant/Research Support)Entasis Therapeutics (Grant/Research Support)E-Scape Bio (Grant/Research Support)Genentech (Grant/Research Support)Geom Therapeutics, Inc. (Grant/Research Support)GlaxoSmithKline (Grant/Research Support)Hoffmann-La Roche (Grant/Research Support)Horizon Orphan LLC (Grant/Research Support)ICPD Biosciences, LLC (Grant/Research Support)Indalo Therapeutics (Grant/Research Support)Insmed Inc. (Grant/Research Support)Institute for Clinical Pharmacodynamics (Employee)Iterum (Grant/Research Support)KBP Biosciences USA (Grant/Research Support)Kyoto Biopharma, Inc. (Grant/Research Support)Matinas (Grant/Research Support)Meiji Seika Pharma Co., Ltd. (Grant/Research Support)Melinta Therapeutics (Grant/Research Support)Menarini Ricerche S.p.A. (Grant/Research Support)Merck & Co., Inc (Grant/Research Support)Mutabilis (Grant/Research Support)Nabriva Therapeutics AG (Grant/Research Support)Naeja-RGM Pharmaceuticals (Grant/Research Support)Nosopharm SAS (Grant/Research Support)Novartis Pharmaceuticals Corp. (Grant/Research Support)NuCana Biomed (Grant/Research Support)Paratek Pharmaceuticals, Inc. (Grant/Research Support)Polyphor, Ltd. (Grant/Research Support)Prothena Corporation (Grant/Research Support)PTC Therapeutics (Grant/Research Support)Rempex Pharmaceuticals (Grant/Research Support)Roche TCRC (Grant/Research Support)Sagimet (Grant/Research Support)scPharmaceuticals Inc. (Grant/Research Support)Scynexis (Grant/Research Support)Spero Therapeutics (Grant/Research Support)TauRx Therapeutics (Grant/Research Support)Tetraphase Pharmaceuticals (Grant/Research Support)Theravance Biopharma Pharmaceutica (Grant/Research Support)USCAST (Grant/Research Support)VenatoRx (Grant/Research Support)Vical Incorporated (Grant/Research Support)Wockhardt Bio AG (Grant/Research Support)Zavante Therapeutics (Grant/Research Support)Zogenix International (Grant/Research Support) Christopher M. Rubino, Pharm.D., 3-V Biosciences (Grant/Research Support)Achogen (Grant/Research Support)Amplyx Pharmaceuticals, Inc. (Grant/Research Support)Arixa Pharmaceuticals (Grant/Research Support)Arsanis Inc. (Grant/Research Support)B. Braun Medical Inc. (Grant/Research Support)Basilea Pharmaceutica (Grant/Research Support)BLC USA (Research Grant or Support)Boston Pharmaceuticals (Grant/Research Support)Bravos Biosciences, LLC (Grant/Research Support, Other Financial or Material Support, member/owner)Cidara Therapeutics Inc. (Grant/Research Support)Cipla, USA (Grant/Research Support)Corcept Therapeutics (Grant/Research Support)Cumberland Pharmaceuticals (Grant/Research Support)Debiopharm International SA (Grant/Research Support)Discuva Limited (Grant/Research Support)Emerald Lake Technologies (Grant/Research Support)Enhanced Pharmacodynamics (Grant/Research Support)Entasis Therapeutics (Grant/Research Support)E-Scape Bio (Grant/Research Support)Genentech (Grant/Research Support)Geom Therapeutics, Inc. (Grant/Research Support)GlaxoSmithKline (Grant/Research Support)Hoffmann-La Roche (Grant/Research Support)Horizon Orphan LLC (Grant/Research Support)ICPD Biosciences, LLC (Grant/Research Support, Other Financial or Material Support, member/owner)Indalo Therapeutics (Grant/Research Support)Insmed Inc. (Grant/Research Support)Institute for Clinical Pharmacodynamics (Employee)Iterum (Grant/Research Support)KBP Biosciences USA (Grant/Research Support)Kyoto Biopharma, Inc. (Grant/Research Support)Matinas (Grant/Research Support)Meiji Seika Pharma Co., Ltd. (Grant/Research Support)Melinta Therapeutics (Grant/Research Support)Menarini Ricerche S.p.A. (Grant/Research Support)Merck & Co., Inc (Grant/Research Support)Mutabilis (Grant/Research Support)Nabriva Therapeutics AG (Grant/Research Support)Naeja-RGM Pharmaceuticals (Grant/Research Support)Nosopharm SAS (Grant/Research Support)Novartis Pharmaceuticals Corp. (Grant/Research Support)NuCana Biomed (Grant/Research Support)Paratek Pharmaceuticals, Inc. (Grant/Research Support)Polyphor, Ltd. (Grant/Research Support)Prothena Corporation (Grant/Research Support)PTC Therapeutics (Grant/Research Support)Rempex Pharmaceuticals (Grant/Research Support)Roche TCRC (Grant/Research Support)Sagimet (Grant/Research Support)scPharmaceuticals Inc. (Grant/Research Support)Scynexis (Grant/Research Support)Spero Therapeutics (Grant/Research Support)TauRx Therapeutics (Grant/Research Support)Tetraphase Pharmaceuticals (Grant/Research Support)Theravance Biopharma Pharmaceutica (Grant/Research Support)USCAST (Grant/Research Support)VenatoRx (Grant/Research Support)Vical Incorporated (Grant/Research Support)Wockhardt Bio AG (Grant/Research Support)Zavante Therapeutics (Grant/Research Support)Zogenix International (Grant/Research Support) Sujata M. Bhavnani, Pharm.D., M.S., FIDSA, 3-V Biosciences (Grant/Research Support)Achogen (Grant/Research Support)Amplyx Pharmaceuticals, Inc. (Grant/Research Support)Arixa Pharmaceuticals (Grant/Research Support)Arsanis Inc. (Grant/Research Support)B. Braun Medical Inc. (Grant/Research Support)Basilea Pharmaceutica (Grant/Research Support)BLC USA (Grant/Research Support)Boston Pharmaceuticals (Grant/Research Support)Bravos Biosciences, LLC (Grant/Research Support, Other Financial or Material Support, member/owner)Cidara Therapeutics Inc. (Grant/Research Support)Cipla, USA (Grant/Research Support)Corcept Therapeutics (Grant/Research Support)Cumberland Pharmaceuticals (Grant/Research Support)Debiopharm International SA (Grant/Research Support)Discuva Limited (Grant/Research Support)Emerald Lake Technologies (Grant/Research Support)Enhanced Pharmacodynamics (Grant/Research Support)Entasis Therapeutics (Grant/Research Support)E-Scape Bio (Grant/Research Support)Genentech (Grant/Research Support)Geom Therapeutics, Inc. (Grant/Research Support)GlaxoSmithKline (Grant/Research Support)Hoffmann-La Roche (Grant/Research Support)Horizon Orphan LLC (Grant/Research Support)ICPD Biosciences, LLC (Grant/Research Support, Other Financial or Material Support, member/owner)Indalo Therapeutics (Grant/Research Support)Insmed Inc. (Grant/Research Support)Institute for Clinical Pharmacodynamics (Employee)Iterum (Grant/Research Support)KBP Biosciences USA (Grant/Research Support)Kyoto Biopharma, Inc. (Grant/Research Support)Matinas (Grant/Research Support)Meiji Seika Pharma Co., Ltd. (Grant/Research Support)Melinta Therapeutics (Grant/Research Support)Menarini Ricerche S.p.A. (Grant/Research Support)Merck & Co., Inc (Grant/Research Support)Mutabilis (Grant/Research Support)Nabriva Therapeutics AG (Grant/Research Support)Naeja-RGM Pharmaceuticals (Grant/Research Support)Nosopharm SAS (Grant/Research Support)Novartis Pharmaceuticals Corp. (Grant/Research Support)NuCana Biomed (Grant/Research Support)Paratek Pharmaceuticals, Inc. (Grant/Research Support)Polyphor, Ltd. (Grant/Research Support)Prothena Corporation (Grant/Research Support)PTC Therapeutics (Grant/Research Support)Rempex Pharmaceuticals (Grant/Research Support)Roche TCRC (Grant/Research Support)Sagimet (Grant/Research Support)scPharmaceuticals Inc. (Grant/Research Support)Scynexis (Grant/Research Support)Spero Therapeutics (Grant/Research Support)TauRx Therapeutics (Grant/Research Support)Tetraphase Pharmaceuticals (Grant/Research Support)Theravance Biopharma Pharmaceutica (Grant/Research Support)USCAST (Grant/Research Support)VenatoRx (Grant/Research Support)Vical Incorporated (Grant/Research Support)Wockhardt Bio AG (Grant/Research Support)Zavante Therapeutics (Grant/Research Support)Zogenix International (Grant/Research Support) Paul G. Ambrose, Pharm.D., FIDSA, 3-V Biosciences (Grant/Research Support)Achogen (Grant/Research Support)Amplyx Pharmaceuticals, Inc. (Grant/Research Support)Arixa Pharmaceuticals (Grant/Research Support)Arsanis Inc. (Grant/Research Support)B. Braun Medical Inc. (Grant/Research Support)Basilea Pharmaceutica (Grant/Research Support)BLC USA (Grant/Research Support)Boston Pharmaceuticals (Grant/Research Support)Bravos Biosciences, LLC (Grant/Research Support, Other Financial or Material Support, member/owner)Cidara Therapeutics Inc. (Grant/Research Support)Cipla, USA (Grant/Research Support)Corcept Therapeutics (Grant/Research Support)Cumberland Pharmaceuticals (Grant/Research Support)Debiopharm International SA (Grant/Research Support)Discuva Limited (Research Grant or Support)Emerald Lake Technologies (Grant/Research Support)Enhanced Pharmacodynamics (Grant/Research Support)Entasis Therapeutics (Grant/Research Support)E-Scape Bio (Grant/Research Support)Genentech (Grant/Research Support)Geom Therapeutics, Inc. (Grant/Research Support)GlaxoSmithKline (Grant/Research Support)Hoffmann-La Roche (Grant/Research Support)Horizon Orphan LLC (Grant/Research Support)ICPD Biosciences, LLC (Grant/Research Support, Other Financial or Material Support, member/owner)Indalo Therapeutics (Grant/Research Support)Insmed Inc. (Grant/Research Support)Institute for Clinical Pharmacodynamics (Employee)Iterum (Grant/Research Support)KBP Biosciences USA (Grant/Research Support)Kyoto Biopharma, Inc. (Grant/Research Support)Matinas (Grant/Research Support)Meiji Seika Pharma Co., Ltd. (Grant/Research Support)Melinta Therapeutics (Grant/Research Support)Menarini Ricerche S.p.A. (Grant/Research Support)Merck & Co., Inc (Grant/Research Support)Mutabilis (Grant/Research Support)Nabriva Therapeutics AG (Grant/Research Support)Naeja-RGM Pharmaceuticals (Grant/Research Support)Nosopharm SAS (Grant/Research Support)Novartis Pharmaceuticals Corp. (Grant/Research Support)NuCana Biomed (Grant/Research Support)Paratek Pharmaceuticals, Inc. (Grant/Research Support)Polyphor, Ltd. (Grant/Research Support)Prothena Corporation (Grant/Research Support)PTC Therapeutics (Grant/Research Support)Rempex Pharmaceuticals (Grant/Research Support)Roche TCRC (Grant/Research Support)Sagimet (Grant/Research Support)scPharmaceuticals Inc. (Grant/Research Support)Scynexis (Grant/Research Support)Spero Therapeutics (Grant/Research Support)TauRx Therapeutics (Grant/Research Support)Tetraphase Pharmaceuticals (Grant/Research Support)Theravance Biopharma Pharmaceutica (Grant/Research Support)USCAST (Grant/Research Support)VenatoRx (Grant/Research Support)Vical Incorporated (Grant/Research Support)Wockhardt Bio AG (Grant/Research Support)Zavante Therapeutics (Grant/Research Support)Zogenix International (Grant/Research Support) Mariana Castanheira, PhD, AbbVie (formerly Allergan ) (Research Grant or Support)Bravos Biosciences (Research Grant or Support)Cidara Therapeutics, Inc. (Research Grant or Support)Cipla Therapeutics (Research Grant or Support)Cipla USA Inc. (Research Grant or Support)GlaxoSmithKline (Research Grant or Support)Melinta Therapeutics, Inc. (Research Grant or Support)Melinta Therapeutics, LLC (Research Grant or Support)Pfizer, Inc. (Research Grant or Support)Qpex Biopharma (Research Grant or Support)Shionogi (Research Grant or Support)Spero Therapeutics (Research Grant or Support) Mariana Castanheira, PhD, Affinity Biosensors (Individual(s) Involved: Self): Research Grant or Support; Allergan (Individual(s) Involved: Self): Research Grant or Support; Amicrobe, Inc (Individual(s) Involved: Self): Research Grant or Support; Amplyx Pharma (Individual(s) Involved: Self): Research Grant or Support; Artugen Therapeutics USA, Inc. (Individual(s) Involved: Self): Research Grant or Support; Astellas (Individual(s) Involved: Self): Research Grant or Support; Basilea (Individual(s) Involved: Self): Research Grant or Support; Beth Israel Deaconess Medical Center (Individual(s) Involved: Self): Research Grant or Support; BIDMC (Individual(s) Involved: Self): Research Grant or Support; bioMerieux Inc. (Individual(s) Involved: Self): Research Grant or Support; BioVersys Ag (Individual(s) Involved: Self): Research Grant or Support; Bugworks (Individual(s) Involved: Self): Research Grant or Support; Cidara (Individual(s) Involved: Self): Research Grant or Support; Cipla (Individual(s) Involved: Self): Research Grant or Support; Contrafect (Individual(s) Involved: Self): Research Grant or Support; Cormedix (Individual(s) Involved: Self): Research Grant or Support; Crestone, Inc. (Individual(s) Involved: Self): Research Grant or Support; Curza (Individual(s) Involved: Self): Research Grant or Support; CXC7 (Individual(s) Involved: Self): Research Grant or Support; Entasis (Individual(s) Involved: Self): Research Grant or Support; Fedora Pharmaceutical (Individual(s) Involved: Self): Research Grant or Support; Fimbrion Therapeutics (Individual(s) Involved: Self): Research Grant or Support; Fox Chase (Individual(s) Involved: Self): Research Grant or Support; GlaxoSmithKline (Individual(s) Involved: Self): Research Grant or Support; Guardian Therapeutics (Individual(s) Involved: Self): Research Grant or Support; Hardy Diagnostics (Individual(s) Involved: Self): Research Grant or Support; IHMA (Individual(s) Involved: Self): Research Grant or Support; Janssen Research & Development (Individual(s) Involved: Self): Research Grant or Support; Johnson & Johnson (Individual(s) Involved: Self): Research Grant or Support; Kaleido Biosceinces (Individual(s) Involved: Self): Research Grant or Support; KBP Biosciences (Individual(s) Involved: Self): Research Grant or Support; Luminex (Individual(s) Involved: Self): Research Grant or Support; Matrivax (Individual(s) Involved: Self): Research Grant or Support; Mayo Clinic (Individual(s) Involved: Self): Research Grant or Support; Medpace (Individual(s) Involved: Self): Research Grant or Support; Meiji Seika Pharma Co., Ltd. (Individual(s) Involved: Self): Research Grant or Support; Melinta (Individual(s) Involved: Self): Research Grant or Support; Menarini (Individual(s) Involved: Self): Research Grant or Support; Merck (Individual(s) Involved: Self): Research Grant or Support; Meridian Bioscience Inc. (Individual(s) Involved: Self): Research Grant or Support; Micromyx (Individual(s) Involved: Self): Research Grant or Support; MicuRx (Individual(s) Involved: Self): Research Grant or Support; N8 Medical (Individual(s) Involved: Self): Research Grant or Support; Nabriva (Individual(s) Involved: Self): Research Grant or Support; National Institutes of Health (Individual(s) Involved: Self): Research Grant or Support; National University of Singapore (Individual(s) Involved: Self): Research Grant or Support; North Bristol NHS Trust (Individual(s) Involved: Self): Research Grant or Support; Novome Biotechnologies (Individual(s) Involved: Self): Research Grant or Support; Paratek (Individual(s) Involved: Self): Research Grant or Support; Pfizer (Individual(s) Involved: Self): Research Grant or Support; Prokaryotics Inc. (Individual(s) Involved: Self): Research Grant or Support; QPEX Biopharma (Individual(s) Involved: Self): Research Grant or Support; Rhode Island Hospital (Individual(s) Involved: Self): Research Grant or Support; RIHML (Individual(s) Involved: Self): Research Grant or Support; Roche (Individual(s) Involved: Self): Research Grant or Support; Roivant (Individual(s) Involved: Self): Research Grant or Support; Salvat (Individual(s) Involved: Self): Research Grant or Support; Scynexis (Individual(s) Involved: Self): Research Grant or Support; SeLux Diagnostics (Individual(s) Involved: Self): Research Grant or Support; Shionogi (Individual(s) Involved: Self): Research Grant or Support; Specific Diagnostics (Individual(s) Involved: Self): Research Grant or Support; Spero (Individual(s) Involved: Self): Research Grant or Support; SuperTrans Medical LT (Individual(s) Involved: Self): Research Grant or Support; T2 Biosystems (Individual(s) Involved: Self): Research Grant or Support; The University of Queensland (Individual(s) Involved: Self): Research Grant or Support; Thermo Fisher Scientific (Individual(s) Involved: Self): Research Grant or Support; Tufts Medical Center (Individual(s) Involved: Self): Research Grant or Support; Universite de Sherbrooke (Individual(s) Involved: Self): Research Grant or Support; University of Iowa (Individual(s) Involved: Self): Research Grant or Support; University of Iowa Hospitals and Clinics (Individual(s) Involved: Self): Research Grant or Support; University of Wisconsin (Individual(s) Involved: Self): Research Grant or Support; UNT System College of Pharmacy (Individual(s) Involved: Self): Research Grant or Support; URMC (Individual(s) Involved: Self): Research Grant or Support; UT Southwestern (Individual(s) Involved: Self): Research Grant or Support; VenatoRx (Individual(s) Involved: Self): Research Grant or Support; Viosera Therapeutics (Individual(s) Involved: Self): Research Grant or Support; Wayne State University (Individual(s) Involved: Self): Research Grant or Support